Paradoxos do visível : reality shows, estética e biopolítica - Marzochi, Ilana Feldman (2011)
Taking an aesthetic and biopolitical perspective, we seek to understand the reality show phenomenon, viewed not only as a set of stand-alone programs, but especially as a cultural and operational logic that takes for granted and tends to consolidate values, practices, and discourses proper to the present-day so-called immaterial or cognitive stage of capitalism. Within this panorama we focus special attention on the Big Brother Brazil narrative format, viewed here as a biopolitical dispositif, both because it takes anonymous and real life itself as the raw material for observation and instrumentalization, and because it represents a technology for subjective production and management. However, while we accept that this biopolitical audiovisual production creates perverse effects, based on extremely unequal power relations whose strategies focus on humiliation and embarrassment, we cannot close our eyes to the program s narrative inventiveness, enhanced with each successive edition of the program, featuring the consolidation of a modern and self-reflexive dramaturgy. Our examination of this paradoxical object thus provides the basis for investigating the true paradox at stake: a demand for reality and a will to truth that shifts the truth from the background, from the foundations of our tradition of thought, to the surfaces of images, simultaneously and paradoxically identifying the image with proof of truth, and truth with an effect of the artifice. The will to truth thus becomes the will to artifice. This effect of truth, or effect of the real, thereby legitimizes and self-validates a series of biopolitical practices, meanwhile taking surveillance and exposure of so-called intimacy for granted. Such practices, tied to a biopolitical audiovisual production, shape our contemporary regime of truth, visibility, and sensitivity within immaterial capitalist production.